High-intensity focused ultrasound as a combined approach for the treatment of recurrent low-grade endometrial stromal sarcoma: a case report and literature review - Chen, Huihui; Shang, Xiaonan; Shen, Yue; Huang, Huajing; Jiang, Zhebo; Wang, Qingyi; Cao, Zhixing; Yan, Peiyu; Xiao, Suying; Chen, Liangyu; Huang, Donghui; Kang, Min (Frontiers in Oncology, 2025)
BackgroundSurgery is the primary treatment for Endometrial Stromal Sarcoma (ESS), however, a substantial proportion of patients with ESS experience recurrence or metastasis. Currently, surgery and local ablation are the main treatments for recurrent ESS followed by chemotherapy, radiotherapy, immunotherapy, targeted therapy, and anti-estrogen therapy. Surgery and local ablation are invasive treatments and may carry risks such as intestinal damage and the risk of massive bleeding from tumor rupture. For patients who refuse or are unable to undergo surgery and local ablation, conservative treatment is not effective, and there is currently no definitive effective non-invasive or combined treatment plan.Case presentationThis report presents a case of a patient with recurrent endometrial stromal sarcoma who refused surgical and local ablation treatments. After receiving HIFU treatment combined with chemotherapy, the progression of the tumor was effectively inhibited, the tumor volume significantly reduced, and liver function was restored during the HIFU period, providing an opportunity for chemotherapy.ConclusionsHIFU combined with chemotherapy may provide a new treatment strategy for patients with recurrent, metastatic endometrial stromal sarcoma, or those who are unsuitable for surgery, local ablation, or those with poor baseline status unable to tolerate intensive chemotherapy.